Neo-slave narratives : studies in the social logic of a literary form - Rushdy, Ashraf H. A., 1961- (Race and American culture., 1999)
"This book studies the political, social, and cultural content of a particular literary form - the novel of slavery cast as a first-person slave narrative. After discerning the social and historical factors surrounding its first appearance in the 1960s, Neo-Slave Narratives explores the complex relationship between nostalgia and critique, while asking how African American intellectuals at different points between 1976 and 1990 remember and use the site of slavery to represent cultural debates that arose during the sixties."--Jacket.